Framing water sensitive urban design as part of the urban form: A critical review of tools for best planning practice. (October 2017) - Kuller, Martijn; Bach, Peter M.; Ramirez-Lovering, Diego; Deletic, Ana
Abstract: Spatial planning for green stormwater treatment technologies, known as Water Sensitive Urban Design (WSUD), is a 'wicked' problem which can greatly benefit from the application of Planning Support Systems (PSS). Our review of currently existing WSUD-PSS shows that WSUD is approached from three perspectives: hydrological, urban planning and water governance. As a form of best (urban) planning practice, WSUD requires PSS that regard these technologies as an integral part of the urban form. We argue that suitability of location for WSUD has two sides: 'WSUD needs a place' and 'a place needs WSUD'. No framework or PSS exists that frames WSUD from both sides of suitability. We propose such a suitability framework, building on evidence from literature. Our review found no comprehensive tool or strategy incorporating all relevant factors for suitability analysis. Our proposed framework addresses this gap, and serves as the basis for rigorous WSUD-PSS. Highlights: Critical review of models, frameworks and tools for sustainable urban water management, and the potential of GIS-MCDA. A comprehensive spatial suitability assessment framework for WSUD placement, that can form the basis for new planning tools. Extending the suitability concept beyond biophysical factors to include socio-economic, planning & governance, local needs. Novel systematic incorporation of ecosystem services into suitability framework for green stormwater systems.